Imaging description of joint effusion in a Colombian creole mare - Gallego Rodríguez, Renso Sneider (2019)
The case of a 15-year-old Colombian equine female, which is presented due to trauma consultation in the medial aspect of the left hind limb is reported. Severe synovial effusion is evidenced with increase in temperature and pain to the touch. An arthrocentesis is performed obtaining hemorrhagic articular fluid. In the radiological evaluation, an increase in the volume and radiopacity of the synovial fluid was observed, and the ultrasound diagnosis revealed an increase in the thickness of the articular capsule, with abundant joint effusion, a heterogeneous-looking fluid and the presence of echogenic bands compatible with fibrin. The therapy consisted in the joint lavage and infiltration with gentamicin, whereas the pain and oedema were treated via systemic.